(untitled) (Conferencea, 2023)
World history shows that power is still an important phenomenon for states. Firstly, simply because in an anarchic environment, where there is no central government, power is an integral part of political relations, and secondly, the power can help the state to achieve not only military but also other types of goals due to its universal nature. States often resort to violence, despite its high cost. In this paper, we analyze the 2008 Russia-Georgia conflict according to Robert Art’s theory about the use of force. We will also consider the most influential concept of the theory of international relations - realism, which has not lost its relevance to this day. The qualitative research method is used in the research, namely case study, which means the analysis of real facts based on the works of different scientists or researchers. The issue is unequivocally relevant and important since we observe that the states are still trying to achieve their goals using force. Russia continues to encroach on the territorial integrity of sovereign states, currently, it is waging an active war against Ukraine, which it attacked on February 24, 2022, and is still trying to conquer.